Career Metaphors and Significant Childhood Experiences in Social Entrepreneurs$1 (BCareer Choices - Hilla Cohen; Oshrit Kaspi Baruch
This article examines the role of childhood experiences and metaphors in social entrepreneurs$1 (B(SEs) career choice processes through a psychoanalytic lens. Metaphors are a unique projective tool to explore SEs$1 (Bsubconscious processes. A total of 104 in-depth semi-structured interviews and 24 in-depth life-story interviews with SEs were conducted based on psychoanalytic theories emphasising family dynamics, childhood experiences and mental processes. The SEs were asked about significant childhood experiences and for a metaphor that describes their occupation. The metaphors they chose were justice fighter, caregiver, creator, leader and martyr. Thematic analysis showed specific recurrent significant negative childhood experiences, especially loneliness, family crisis and abuse and feeling lost, among others. Analysis revealed strong correspondence between specific metaphors and childhood experiences. Interpreted through a psychoanalytic lens, these findings denote compensation processes that underlie career choices and offer a deeper understanding of how and why SEs choose, develop and narrate their careers. In conclusion, using such psychoanalytical tools is recommended in SEs$1 (Bcareer training.s